Towards recycling cost modelling framework for carbon fibre composites - Shehab, Essam; Alanazi, Ghunaim; Sarfraz, Shoaib (IOS Press, 2019)
Environmental legislation puts more pressure on solving carbon fibre composites (CFC) waste management through recycling and reuse. Despite their superior properties, CFC creates environmental issue when it reaches its end of life. The aim of this paper is to to provide a framework that represents the first step towards the development of a cost modelling framework for recycling CFC materials. The focus is the mechanical and thermal (Pyrolysis) recycling process. The activities and the tasks related to each recycling process are presented. The research has been accomplished by embracing a qualitative research plan consisting of five phases. To enhance understanding of the parameters affecting the cost of the recycling process, the major and detailed cost drivers are recognised. The developed costing framework has been implemented in an IT-based cost estimation tool for easy handling and calculation of the cost parameters. This tool identifies all tasks and activities related to the two recycling processes.
Keywords: Mechanical and Thermal Recycling; Cost Modelling; Carbon Fibre; Composites